Perceptions of changes made to a clinical skills curriculum in a medical programme in South Africa: a mixed method study. - Pattinson, Stuart Redvers (My University, 2018)
In 2015 the University of the Witwatersrand’s Medical Curriculum was reviewed. The reports identified that there was too large a gap between the Medical School based teaching in the second year of the programme and the hospital-based teaching in the third year when the students begin their clinical clerkships. A number of changes, based on current evidence, were made to the curriculum in order to try to remedy these important concerns for the accreditation of the programme and prepare the students better for the expectations of the clinical setting. An exploratory mixed methods approach was used to determine the perceptions of the students and the clinical teachers of the new curriculum, in respect to how well it prepares them for their clinical years, comparing the students taught under the new and old curricula respectively. Phase one was a narrative qualitative study; the narrative data were analysed using a qualitative approach and the categories that emerged informed the development of a questionnaire for phase two which was a cross-sectional, comparative, quantitative study. The results showed a statistically significant improvement of the perceptions of the third-year students of their preparedness for the clinical setting when compared to the fourth-year students who were taught under the old curriculum. The teachers’ data showed no difference between the two groups. The new curriculum has resulted in a significant improvement (p value = 0) of the students’ perceived preparation for their clinical clerkships.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Health Science Education, Johannesburg October 2018
Keywords: Medical Curriculum; Clinical Clerkship